PENINGKATAN KEMAMPUAN BERBICARA PADA ANAK USIA 5-6 TAHUN DI TK PERTIWI KECAMATAN KENDAWANGAN - (F54210012), Ernawati; Endang, Busri; ., Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Based on the findings that : 1 ) Planning learning in enhancing the development of the ability to speak through conversing methods can be categorized as performing well , because teachers make plans that facilitate the delivery of content. 2 ) Implementation of learning in improving the ability to talk through the method of conversing among others: a) Footing environment b ) Footing before playing, c ) Footing while playing, d ) Footing after play. 3 ) Increasing the ability to talk through method conversing in children aged 5-6 years include: speaking with correct pronunciation and the sound increased to 73% . While the child's ability to understand the spoken word sound increased to 73 % . The ability of crafting a good kid in the story reveals increased to 73 % . The results of this study can be concluded that learning in enhancing the development of the ability to speak through conversing methods can be categorized as performing well, because teachers make the planning , implementation and can increase the child's ability to speak to one cycle of 60 % and the cycle 2 increased to 73%. To carry out the study , especially in improving the speech of children aged 5-6 years with the adoption of a conversation, the teacher should be able to design a useful approach in motivating children to learn in order to speak the child's ability to thrive as it should . Keywords : Speech , Conversation Method Abstrak: Berdasarkan hasil penelitian bahwa: 1) Perencanaan pembelajaran dalam meningkatkan pengembangan kemampuan berbicara melalui metode bercakap-cakap dapat dikategorikan terlaksana dengan baik, karena guru membuat perencanaan yang memudahkan dalam penyampaian materi. 2) Pelaksanaan pembelajaran dalam meningkatkan kemampuan berbicara melalui metode bercakap-cakap antara lain:a) Pijakan lingkungan b) Pijakan sebelum main c) Pijakan saat main d) Pijakan setelah main. 3) Peningkatan kemampuan berbicara melalui metode bercakap-cakap pada anak usia 5-6 tahun antara lain: berbicara dengan lafal dan bunyi yang benar meningkat menjadi 73%. Sedangkan kemampuan anak memahami bunyi kata yang diucapkan meningkat menjadi 73%. Kemampuan anak menyusun kata yang baik dalam mengungkapkan isi cerita meningkat menjadi 73%. Kata Kunci : Kemampuan Berbicara, Metode Bercakap-cakap